Robust fault tolerant control of continuous-time switched systems: An LMI approach. (February 2021) - Ait Ladel, Ayyoub; Benzaouia, Abdellah; Outbib, Rachid; Ouladsine, Mustapha; El Adel, El Mostafa
Abstract: The present paper proposes a new robust fault tolerant control (RFTC) design for continuous-time switched systems. The main objective is to design in an integrated way the couple (controller, observer) that allows to stabilize switched systems even in the presence of actuator faults. A state/fault estimation observer is designed to simultaneously estimate system state and actuator faults. Based on this observer, a fault tolerant controller is developed to stabilize the system and accommodate the actuator faults automatically. The RFTC problem is formalized in the form of linear matrix inequalities (LMI) rather than bilinear matrix inequalities (BMI), to avoid the difficulty of solving BMIs. Finally, a numerical example composed of unstable subsystems is studied to show the applicability and efficiency of the obtained results. Highlights: Robust stabilization of continuous-time switched systems. Simultaneous estimation of system states and actuator faults. Integrated state/fault estimation observer and fault tolerant controller design. New LMI formalization of the integrated observer and controller design.